A STRATEGY FOR INTRODUCING DIGITAL TECHNOLOGIES AND MODERN METHODS INTO THE EDUCATIONAL PROCESS - Ismatullaeva Raykhona Otabek qizi (Western European Studies, 2024)
This article is devoted to the use of strategies and modern methods of introducing digital technologies and modern methods into the educational process in the educational system. Examples of the use of modern educational technologies in the teaching of information technologies are considered. Also, modern methods that help to improve the qualifications of teachers have been thoroughly studied.
Keywords: modern pedagogical technologies; mass open education technology; online educational platforms